Anodic Sb2S3 electrodeposition from a single source precursor for resistive random-access memory devices. (10th November 2022) - Wallace, A.G.; King, R.P.; Zhelev, N.; Jaafar, A.H.; Levason, W.; Huang, R.; Reid, G.; Bartlett, P.N.
Highlights: For the first time, Sb2 S3 was electrodeposited from a single source precursor at anodic potentials in a non-acidic electrolyte. The voltammetry of the [SbS4 ] 3− anion was explored. A pulsed electrodeposition allowed for the electrodeposition of a Sb2 S3 film free of by-product. Sb2 S3 was demonstrated to be suitable for RRAM applications. Abstract: In this paper we report the use of Na3 [SbS4 ].9H2 O as a single source precursor for the electrodeposition of Sb2 S3 from aqueous electrolyte at pH 9.1. We present the electrochemistry of the [SbS4 ] 3− anion and the redox processes observed for the deposited Sb2 S3 film. We show that an amorphous Sb2 S3 film can be deposited by anodic electrodeposition onto glassy carbon and that the by-product that accompanies this deposition can be avoided by using a suitable pulse plating approach. Raman spectroscopy and grazing incidence X-ray diffraction were used to characterise the deposits and to show that good quality crystalline films of Sb2 S3 are produced on annealing. The crystalline Sb2 S3 films were screened for application in Resistive Random-Access Memory, and it was demonstrated that crystalline Sb2 S3 films display typical bipolar resistive switching behaviour, and that the resistance ratio between the high resistance state and the low resistance state is approximately one order of magnitude at 1.5 V, which is sufficient for memory applications. A mechanism for the resistive switching is also proposed. Graphical abstract: Image, graphical abstract